A recombinant oncolytic Newcastle virus expressing MIP-3α promotes systemic antitumor immunity. Issue 2 (5th August 2020) - Huang, Feng-Ying; Wang, Jin-Yan; Dai, Shu-Zhen; Lin, Ying-Ying; Sun, Yan; Zhang, Liming; Lu, Zhuoxuan; Cao, Rong; Tan, Guang-Hong
Abstract : Background: The oncolytic Newcastle disease virus (NDV) is inherently able to trigger the lysis of tumor cells and induce the immunogenic cell death (ICD) of tumor cells and is also an excellent gene-engineering vector. The macrophage inflammatory protein-3α (MIP-3α) is a specific chemokine for dendritic cells (DCs). Thus, we constructed a recombinant NDV expressing MIP-3α (NDV-MIP3α) as an in vivo DC vaccine for amplifying antitumor immunities. Methods: The recombinant NDV-MIP3α was constructed by the insertion of MIP-3α cDNA between the P and M genes. Western blotting assay and ELISA were used to detect MIP-3α, HMGB1, IgG, and ATP in the supernatant and sera. The chemotaxis of DCs was examined by Transwell chambers. The phenotypes of the immune cells (eg, DCs) were analyzed by flow cytometry. The antitumor efficiency of NDV-MIP3α was observed in B16 and CT26 tumor-bearing mice. Immunofluorescence and immunohistochemistry were applied to observe the ecto-calreticulin (CRT) and intratumoral attraction of DCs. Adoptive transfer of splenocytes and antibodies and depletion of T-cell subsets were used to evaluate the relationship between antitumor immunities and the role of the T-cell subtype. Results: The findings show that NDV-MIP3α has almost the same capabilities of tumor lysis and induction of ICD as the wild-type NDV (NDV-WT). MIP-3α secreted by NDV-MIP3α could successfully attract DCs in vitro and in vivo. Both B16 and CT26 cells infected with NDV-MIP3α could strongly promote DC maturation and activation. Compared with NDV-WT, intratumoral injection of NDV-MIP3α and the adoptive transfer of T lymphocytes from mice injected with NDV-MIP3α resulted in a significant suppression of B16 and CT26 tumor growth. The NDV-MIP3α-induced production of tumor-specific cellular and humoral immune responses was dependent on CD8 + T cells and partially on CD4 + T cells. A significant reversion of tumor microenvironments was found in the mice injected with NDV-MIP3α. Conclusions: Compared with NDV-WT, the recombinant NDV-MIP3α as an in vivo DC vaccine demonstrates enhanced antitumor activities through the induction of stronger system immunities and modulation of the tumor microenvironment. This strategy may be a potential approach for the generation of an in vivo DC vaccine.